Investigating the dynamic interplay of vertical and horizontal spirituality on gratitude in emerging adolescents - Khalili, Nadia (International journal of children's spirituality, 2025)
The approach to adolescence (8–12 years of age) is a transitional and sensitive time in all areas of development including neurobiological, emotional, social, moral and spiritual. However, little is known about the complex interactions between the social and cognitive factors related to adolescents’ beliefs and attitudes towards spirituality and gratitude. This study examined emerging adolescents’ perceptions of spirit, mind, emotion, and behaviour (N = 84, 12–14.18 years, M = 12.8, SD = 5.454 months) as part of a larger longitudinal study on social cognition and well-being in Canadian youth. Hierarchical multiple regressions revealed that high levels of spiritual well-being and perceptions of spiritual lives were positive predictors of high levels of gratitude and happiness (e.g. sense of abundance and appreciation for others). Implications for positive youth development and spiritual health are discussed.